2013
DOI: 10.1108/scm-11-2012-0366
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach for modelling supply chain risks

Abstract: Purpose -With increasing exposure to disruptions, it is vital for supply chains to manage risks proactively. Prediction of potential failure points and overall impact of these risks is challenging. In this paper, systems thinking concepts are applied for modelling supply chain risks. The purpose of this paper is to develop a holistic, systematic and quantitative risk assessment process for measuring the overall risk behaviour. Design/methodology/approach -A framework for supply chain risk management (SCRM) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
131
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 64 publications
0
131
0
1
Order By: Relevance
“…Chopra and Sodhi (2004) suggested that flexible supply base and strategic stocks are the two strategies that can mitigate disruptions. Ghadge et al (2013) found flexible supply base as a way to cope with geopolitical risks. Ritchie and Brindley (2007) differentiate risks by 'high' vs. 'low' only.…”
Section: Risk Mitigation Strategies In Scrmmentioning
confidence: 99%
See 1 more Smart Citation
“…Chopra and Sodhi (2004) suggested that flexible supply base and strategic stocks are the two strategies that can mitigate disruptions. Ghadge et al (2013) found flexible supply base as a way to cope with geopolitical risks. Ritchie and Brindley (2007) differentiate risks by 'high' vs. 'low' only.…”
Section: Risk Mitigation Strategies In Scrmmentioning
confidence: 99%
“…SCRM frameworks suggest categorising strategies by different dimensions, including redundancy vs. flexibility (Chang et al 2015;Kleindorfer and Saad, 2005;); reducing vs. coping (Ghadge et al 2012;Knemeyer et al 2009;Simangunsong et al 2012), such as sharing and transferring (Ghadge et al 2013); monitoring vs. collaboration (Hajmohammad and Vachon 2016); and depending on what risks they are to handle (Chopra and Sodhi, 2004;Ghadge et al 2013;Ho et. al 2015;Lavastre et.…”
Section: "Where Is the Crisis Management Component Of [Humanitarian Omentioning
confidence: 99%
“…contribute to the development of the interaction between the two variables, and the analysis of its process structure is clear and definite [33]. The system dynamics can simulate the function of the two variables with the help of the computer, and observe d.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, the SCRM process is described in similar ways, which can vary from risk identification and/or measurement, risk assessment and/or risk evaluation to mitigation plans and control and/or monitoring (Hallikas et al, 2002;Neiger et al, 2003;Jüttner et al 2005;Kleindorfer and Saad 2005;Tse et al, 2005;Cucchiella and Gastaldi, 2006;Ritchie and Brindley, 2007;Adhitya et al, 2008;Knemeyer et al, 2009;Giannakis and Louis, 2011;Tummala and Schoenherr, 2011;Kern et al, 2012;Ghadge et al, 2013;Ceryno et al, 2014;Elleuch et al, 2014). Different systems have been put forward but most approaches for SCRM process tend to follow the generic process shown in Figure 4.…”
Section: Supply Chain Risk Management (Scrm)mentioning
confidence: 99%
“…This involves a comprehensive and structured determination of potential SC risks associated with the given problem. The main focus of supply chain risk identification is to recognize SC uncertainties in order to enable an efficient risk management (Hallikas et al, 2000;Norrman and Jansson, 2004;Kleindorfer and Saad, 2005;Cucchiella and Gastaldi, 2006;Ritchie and Brindley, 2007;Pujawan and Geraldin, 2009;Blome and Schoenherr, 2011;Kern et al, 2012;Ghadge et al, 2013;Ceryno et al, 2014).…”
Section: Supply Chain Risk Management (Scrm)mentioning
confidence: 99%